Zinc transporter SLC39A13/ZIP13 facilitates the metastasis of human ovarian cancer cells via activating Src/FAK signaling pathway - Xinxin Cheng; Jie Wang; Chunling Liu; Tianduo Jiang; Ningzhi Yang; Dan Liu; Huanhuan Zhao; Zhelong Xu (Journal of Experimental & Clinical Cancer Research, 2021)
Abstract Background Zinc transporters have been found to be associated with the pathogenesis of numerous human diseases including cancer. As the most lethal gynecologic malignancy, ovarian cancer is characterized by rapid progression and widespread metastases. However, the function and underlying mechanism of zinc transporters in ovarian cancer metastasis remain unclear. Methods The relationship between zinc transporter gene expressions and clinical outcomes of ovarian cancer was assessed with the online database Kaplan-Meier plotter ( http://kmplot.com/analysis/ ). Immunohistochemistry was performed to investigate the prognostic importance of ZIP13. The expression of ZIP13 in ovarian cancer cell lines was depleted to explore its effect on proliferation, adhesion, migration, and invasion both in vitro and in vivo assays. RNA-Seq, quantitative RT-PCR, and western blot analysis were performed to explore ZIP13-regulated downstream target genes. Results The expressions of several zinc transporters were highly associated the clinical outcomes of ovarian cancer patients. Among them, high ZIP13 expression was an independent prognostic factor for poor survival in patients with ovarian cancer. ZIP13 knockout suppressed the malignant phenotypes of ovarian cancer cells both in vitro and in vivo. Further investigation revealed that ZIP13 regulated intracellular zinc distribution and then affected the expressions of genes involved in extracellular matrix organization and cytokine-mediated signaling pathway. This led to the activation of Src/FAK pathway with increased expressions of pro-metastatic genes but decreased expressions of tumor suppressor genes. Conclusions ZIP13 is shown to be a novel driver of metastatic progression by modulating the Src/FAK signaling pathway, which may serve as a promising biomarker for prognostic evaluation and targeted therapy in ovarian cancer.